Predicting leisure time physical activity in Finnish school students : a longitudinal study of the trans-contextual model - Hansen, Maiken Rømer (2018)
Considering the consequences of inactivity among children, a central question is how to motivate them to become more physically active. The trans-contextual model (TCM) explains how autonomy support in one context lead to autonomous forms of motivation in the same context which can then transfer to other contexts. There is considerable research demonstrating links between autonomy supportive environment and student autonomous motivation and adaptive outcomes in class. However, comparatively less research has focused on the role of autonomy support in PE setting on children’s behavior outside of school and no other studies have investigated the effect of time of the TCM variables. Thus, the aim of this study was to investigate the effect of time on the motivational sequence of the TCM. Participants were 277 students aged 12-16 years from two Finnish secondary schools. Scales based on the Perceived Locus of Causality Questionnaire and the Theory of Planned Behavior Questionnaire, and self-reported PA level were distributed wice 4 weeks apart. Data were analyzed using SPSS for correlations and regression analysis of the change score variables calculated as the results from time 1 subtracted from results from time 2. Results showed only minor changes between the two time points. In general, relatively low R squared values of the change score variables were found, with the strongest predictor variable being change in autonomous motivation in leisure time (LT) explaining 15% of the variance in change in intention. Especially interesting for the TCM, change in autonomous motivation in class explained 13% of the variance in change in autonomous motivation in LT. In conclusion, results supported the hypotheses demonstrating the TCM´s efficacy in explaining variance in model variables. Future research implementing an intervention is needed to obtain a more complete understanding of the motivational sequence proposed by the model and the effect of autonomy support in PE on LT PA participation.